[PP.21.11] REFERENCE VALUES AND DISTRIBUTION OF THE NEUTROPHIL TO LYMPHOCYTE RATIO IN A LARGE-SCALE POPULATION. (September 2016) - HUGUET, E.; Maccallini, G.; Pardini, P.; Hidalgo, M.; Obregon, S.; Haehnel, M.; Carrizo, P.; Koretzky, M.; Di Leva, A.; Inserra, F.; Botto, F.; Kotliar, C.
Abstract : Objective: During the last years, the Neutrophil to Lymphocyte Ratio (NLR) as a biomarker of inflammation has spread out its clinical application. Recent publications have confirmed its strong and positive predictive value for poor prognosis in diabetes and cardiovascular disease, and the development of hypertension. However, evidence is scarce regarding the average NLR and its distribution in the general population. Our aim was to describe the distribution of the NLR in a large-scale population classified by age and gender. Design and method: We analyzed data from consecutive non-hospitalized subjects over 16 years-old. Blood samples were drawn as part of general medical check-ups in 22 centers during 3 months of 2015, and analyzed in one central lab in 3 hematology analyzers (LH 750, Beckman Coulter). Internal quality controls of third opinion (Bio Rad) were used and subsequent monthly verification procedures of analytical bias were performed. NLR was calculated by dividing the number of neutrophils by number of lymphocytes. Then, NLR was classified and evaluated by gender and decades of life. Results: We included 71, 873 subjects (ranged from 16 to 103 years, 66, 1% female). Males had a NLR median between 1.50 (16 to 19years group) and 2.52 (>90 years group), with a gradual and constant increase between both ends. Women had a NLR median between 1.54 (16 to 19 years group) and 2.38 (>90 years group), with a first peak of NLR in the 30 to 49 years group (p < 0.001 compared with men at same age), and then a progressive increase similar to men. Conclusions: To the extent of our knowledge this is the first time that NLR distribution is explored in a large-scale population by gender and age. A direct and positive association was observed across lifespan in both genders. We hypothesized that an immuno-inflammatory component accompanying arterial aging and atherosclerosis may be the responsible physiopathology. The increase of NLR in the fertile stage of women deserves further research.